2019
DOI: 10.1002/anie.201813048
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Azaproline Confers pH Responsiveness and Functionalizability on Collagen Triple Helices

Abstract: Proline derivatives bearing substituents at Cγ are valuable tools for biological and materials investigations. However, the stereochemistry at Cγ can produce undesired steric or stereoelectronic interactions. Here, we introduce γ‐azaproline (γ‐azPro), which lacks a stereogenic center at Cγ, as a pH‐responsive and functionalizable proline analogue that can adapt to its environment. Conformational analyses by NMR spectroscopy and DFT calculations revealed that the imidazolidine ring of γ‐azPro is flexible. Incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 61 publications
3
58
0
Order By: Relevance
“…However, the ethoxy groups in Ac‐ (EtO) 2 ‐ProM1 ‐OMe were found to be radially oriented, pointing away from the triple helix axis. In addition to existing methods for triple‐helix functionalization, the (HO) 2 ‐ProM1 scaffold might be used for double functionalization by O‐alkylation. In conclusion, the steric demand of the linker group was determined to be crucial for the thermal stability of ProM‐modified CMPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ethoxy groups in Ac‐ (EtO) 2 ‐ProM1 ‐OMe were found to be radially oriented, pointing away from the triple helix axis. In addition to existing methods for triple‐helix functionalization, the (HO) 2 ‐ProM1 scaffold might be used for double functionalization by O‐alkylation. In conclusion, the steric demand of the linker group was determined to be crucial for the thermal stability of ProM‐modified CMPs.…”
Section: Resultsmentioning
confidence: 99%
“…As steric repulsion within the triple helix could explain this result, [39] the DFT-optimized structures of Ac-(EtO) 2 -ProM1-OMe and Ac-(EtO) 2 -ProM2-OMe were aligned with (PPG) 10 to describe the steric situation in the corresponding collagen model peptides.T he alignments (Figure 7) showed that the ethoxy groups in Ac-(EtO) 2 -ProM2-OMe indeed clash with apreceding carbonyl group of the same strand and ap roline ring of an eighboring strand. However,t he ethoxy groups in Ac-(EtO) 2 -ProM1-OMe were found to be radially oriented, pointing away from the triple helix axis.Inaddition to existing methods for triple-helix functionalization, [41][42][43] the (HO) 2 -ProM1 scaffold might be used for double functionalization by O-alkylation. In conclusion, the steric demand of the linker group was determined to be crucial for the thermal stability of ProM-modified CMPs.…”
Section: Analysis Of Structure-stability Relationshipsmentioning
confidence: 99%
“…[13] The K t/c values at basic pH are 1.3 andt husl ower than that of the non-alkylated derivative 1 (K t/c = 3.3). [12] Upon protonation, the trans/cis ratios of 2 and 3 increase( K t/c = 2.2 for Ac-g-azPro(Et)-OMe; K t/c = 1.7 for Ac-g-azPro(Me)-OMe) and are slightly larger than that of g-azPro 1 (K t/c = 1.4).…”
Section: Nmr Spectroscopic Analysis Of Alkylated G-azpro Model Compoundsmentioning
confidence: 98%
“…Reductivea minationo fA c-g-azPro-OMe 1 provided the methylateda nd ethylated g-azPro derivatives 2 and 3 for conformational analysis andc omparison to 1. [12] NMR spectroscopic analyses of 2 and 3 in D 2 Ou nder basic (pH 11) and acidic conditions (pH 2) gave trans/cis amide bond ratios in the range of 1.3-2.2 that are typical for pseudoprolines ( Figure 2b). [13] The K t/c values at basic pH are 1.3 andt husl ower than that of the non-alkylated derivative 1 (K t/c = 3.3).…”
Section: Nmr Spectroscopic Analysis Of Alkylated G-azpro Model Compoundsmentioning
confidence: 99%
See 1 more Smart Citation